2015
DOI: 10.1097/anc.0000000000000228
|View full text |Cite
|
Sign up to set email alerts
|

Got (the Right) Milk? How a Blended Quality Improvement Approach Catalyzed Change

Abstract: As in the realm of pharmacy, the processes involved in preparing feedings for critically ill infants should be carried out via predictable, reliable means including robust automated verification that integrates seamlessly into existing processes. The use of systems employed in pharmacy for medication preparation should be considered in the human milk and formula preparation setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Of the 11 included documents, six were published primary research studies [ 42 , 43 , 45 , 47 49 ], two were published quality improvement case studies [ 44 , 46 ], and three were unpublished quality improvement case reports [ 50 – 52 ] found from our citation searching [ 51 ] and gray literature searching [ 50 , 52 ] (Table 1 ). Of the 11 documents, seven used Lean exclusively [ 44 , 45 , 48 – 52 ]; two used Lean and Six Sigma [ 42 , 43 ]; one used a combination of Lean, Six Sigma, and the Institute for Healthcare Improvement (IHI) Model for Improvement [ 46 ]; and another used Lean with “other” QI classic methods [ 47 ]. Improvements were targeted at the meso (e.g., unit or organization level) ( n = 8) [ 42 49 ] and macro (e.g., policy, system) ( n = 3) [ 50 – 52 ] levels of the healthcare system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 11 included documents, six were published primary research studies [ 42 , 43 , 45 , 47 49 ], two were published quality improvement case studies [ 44 , 46 ], and three were unpublished quality improvement case reports [ 50 – 52 ] found from our citation searching [ 51 ] and gray literature searching [ 50 , 52 ] (Table 1 ). Of the 11 documents, seven used Lean exclusively [ 44 , 45 , 48 – 52 ]; two used Lean and Six Sigma [ 42 , 43 ]; one used a combination of Lean, Six Sigma, and the Institute for Healthcare Improvement (IHI) Model for Improvement [ 46 ]; and another used Lean with “other” QI classic methods [ 47 ]. Improvements were targeted at the meso (e.g., unit or organization level) ( n = 8) [ 42 49 ] and macro (e.g., policy, system) ( n = 3) [ 50 – 52 ] levels of the healthcare system.…”
Section: Resultsmentioning
confidence: 99%
“…No improvement targeted the individual, micro level. Documents focused on a variety of problems, clinical ( n = 1) [ 42 ], process ( n = 2) [ 43 , 48 ], clinical and process (n = 1) [ 46 ], or process and system problems ( n = 7) [ 44 , 45 , 47 , 49 – 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infants fed with mother's milk are also less prone to develop metabolic syndrome, low BP, or fewer LDL levels in the later stages of their life. 42 Luton et al, 43 have demonstrated a 83% reduction in the errors associated with feeding the preterm infants in NICU through a proven quality improvement initiative. The expression of human milk and its storage and fortification in this NICU was carefully monitored by the quality improvement team to avoid feeding errors.…”
Section: Breast Milk Nutritionmentioning
confidence: 99%
“…Luton et al 43 Breast milk nutrition Expression of human milk, its storage and fortification in this NICU were carefully monitored Reduction in the human milk errors Meier et al 44 Oza-Frank et al 45 Liu et al, 46 Boyd et al, 47 Cristofalo et al 48…”
mentioning
confidence: 99%